2019
DOI: 10.1027/1016-9040/a000372
|View full text |Cite
|
Sign up to set email alerts
|

The Human Right to Make One’s Own Choices – Implications for Supported Decision-Making in Persons With Dementia

Abstract: Abstract. Autonomy is a human right and implies the “freedom to make one’s own choices.” The UN Convention on the Rights of Persons with Disabilities (UN-CRPD) is a human rights treaty granting persons with disabilities, such as persons with dementia (PwD), legal capacity regardless of their impairments. State parties and healthcare practitioners (HCP) are obliged to enable PwD to make decisions with legal effect. The UN-CRPD does not specify the nature of support, thus, the implementation of supported decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Our review showed HCPs were sensitive to PLwD's need for autonomy and independence and supported risk enablement in care planning where possible. Similarly, Wied et al (2019) found that HCPs do not deny PLwD their right to make their own decisions and they are supported with decisionmaking in terms of care. A key challenge for HCPs is communication with PLwD and carers when perceptions of risk differ or there is lack of insight (Stevenson and Taylor, 2017).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our review showed HCPs were sensitive to PLwD's need for autonomy and independence and supported risk enablement in care planning where possible. Similarly, Wied et al (2019) found that HCPs do not deny PLwD their right to make their own decisions and they are supported with decisionmaking in terms of care. A key challenge for HCPs is communication with PLwD and carers when perceptions of risk differ or there is lack of insight (Stevenson and Taylor, 2017).…”
Section: Discussionmentioning
confidence: 97%
“…It is essential to balance independence and risks when planning care (Mitchell and Glendinning, 2008;Taylor, 2006), and PLwD want to and should be involved in that decision-making process (Pel-Littel et al, 2021;Wied et al, 2019). Effective risk identification and assessment can inform the most appropriate way to manage risk and promote risk enablement that involves balancing the rights of PLwD to retain as much control as possible, with those of society and families' wishes to reduce risks and promote safety at home.…”
Section: Introductionmentioning
confidence: 99%